Fossil coleoid cephalopod from the Mississippian Bear Gulch Lagerstätte sheds light on early vampyropod evolution - Christopher D. Whalen; Neil H. Landman (Nature Communications, 2022)
Abstract We describe an exceptionally well-preserved vampyropod, Syllipsimopodi bideni gen. et sp. nov., from the Carboniferous (Mississippian) Bear Gulch Lagerstätte of Montana, USA. The specimen possesses a gladius and ten robust arms bearing biserial rows of suckers; it is the only known vampyropod to retain the ancestral ten-arm condition. Syllipsimopodi is the oldest definitive vampyropod and crown coleoid, pushing back the fossil record of this group by ~81.9 million years, corroborating molecular clock estimates. Using a Bayesian tip-dated phylogeny of fossil neocoleoid cephalopods, we demonstrate that Syllipsimopodi is the earliest-diverging known vampyropod. This strongly challenges the common hypothesis that vampyropods descended from a Triassic phragmoteuthid belemnoid. As early as the Mississippian, vampyropods were evidently characterized by the loss of the chambered phragmocone and primordial rostrum—traits retained in belemnoids and many extant decabrachians. A pair of arms may have been elongated, which when combined with the long gladius and terminal fins, indicates that the morphology of the earliest vampyropods superficially resembled extant squids.